NATO opportunities in the MENA region in the context of the Russian threat - Teodora-Ioana MORARU (Bulletin of "Carol I" National Defense University)
The Middle East and North Africa (MENA) region represents a geopolitical space marked by instability, strategic competition and the influence of global actors, including the Russian Federation, which has strengthened its presence through economic and military partnerships, as well as information influence campaigns. In this context, the North Atlantic Treaty Organization (NATO) can adopt new strategies to expand its engagement in the region, aiming to counter these dynamics and reduce Russia’s ability to destabilize Euro-Atlantic security. This study employs prospective analysis methods, specifically the RVAP-O framework (Risks, Vulnerabilities, Threats and Opportunities) to identify the main challenges and possible courses of action in the MENA region and the environmental scanning/horizon scanning (ES/HS) method to assess their shortterm impact. Thus, the research examines the extent to which NATO’s involvement in MENA can alter the balance of power and reshape the Russian Federation’s strategic priorities, thereby limiting its operational capabilities in the Euro-Atlantic space.